Occupational Therapists and COVID-19 Pandemic: An Observational Survey in Europe - Christian Pozzi; Alessandro Lanzoni; Pier Carlo Battain; Evelyn Alvarez; Eduardo Tobar; Ruth Hersche; Stefano Cavalli; Anna Monsò; Eva Llarch; Giuseppe Bellelli; Alessandro Morandi; Maud Graff (Scholarworks @ WMU, 2022)
Background: The COVID-19 pandemic has resulted in a health care emergency in Europe since the first wave in 2020. Several challenges have arisen for occupational therapists, as well as all the health care professionals. The aim of this study was to determine what occupational therapists have changed to adapt their therapeutic processes for this catastrophic situation. Method: An online survey was developed and sent in conjunction with the Council of Occupational Therapy for European Countries (COTEC) to European national associations of occupational therapists. Results: The study was based on a sample of 65 occupational therapists who worked with people with COVID-19. More than half of the occupational therapists (54.8%) had changed departments. The main needs patients expressed (n = 136) during hospitalization were to have social contacts (30.9%), and the main clinical complaints (n = 144) were motor impairment and fatigue (35.4%) and depression (25.7%). The most frequently reported goal (n = 141) was recovery of physical performance and fatigue management (32.6%). Among the emotions mentioned by occupational therapists, negative emotions (76%) were the most common. Conclusion: European occupational therapists demonstrated flexibility and resilience to deal with clinical and organizational challenges during the COVID-19 emergency